Comparative analysis of desiccation responses in three Xerophyta species at two stages of seedling development - Ngcala, Mamosa (Department of Molecular and Cell Biology, 2025)
Vegetative desiccation tolerance (VDT) is a rare trait among flowering plants, enabling the adult tissues of certain species, known collectively as resurrection plants, to survive near-total water loss and revive upon rehydration. This study used a seedling model to investigate VDT at two developmental stages, pre-leaf and two-leaf stage, across three Xerophyta species: the poikilochlorophyllous Xerophyta schlechteri, and X. humilis, and the homoiochlorophyllous X. elegans. By analyzing changes in cellular ultrastructure, gene expression, and metabolite and lipid concentrations, the aim was to identify core conserved VDT mechanisms in these three Xerophyta species, as well as differences between poikilochlorophyllous and homoiochlorophyllous species in the same genus. Transcriptomic analysis showed that the key seed master maturation transcription factors (TFs) ABI3A and ABI5A, were up-regulated in dry pre-leaf seedlings but no expression was detected in two-leaf seedlings. In contrast, the ABRE binding factor, ABFA, was highly expressed in dry tissues at all developmental stages across all species, suggesting a potential role in VDT. A three-way comparison was used to identify gene orthogroups (OGs) that showed the same response to desiccation across all three Xerophyta species: these 370 up-regulated and 335 down-regulated OGs potentially represented a core set of desiccation-responsive genes in Xerophyta species. Promoter regions of these core OGs were enriched with binding sites for Xerophyta specific expanded TF families, including Heat Shock Factors (HSFs), A-T hook factors (AHLs), and C2H2 Zinc Finger Proteins (ZATs). The gene ontology enrichment showed that the HSF, AHL, and ZAT motif containing OGs that were up-regulated are involved in water deprivation, abscisic acid response, and oxidative stress response processes, whereas the down-regulated OGs are involved in growth and development related processes. Notably, some of the up-regulated HSF motif-containing target OGs included WRKY TFs, stachyose synthase, and solanesyl diphosphate synthase 2, which are involved in stress-related functions enhancing VDT. Metabolite analysis demonstrated that the osmoprotectants proline, sucrose, and trehalose accumulated in dry tissues at both developmental stages of all three Xerophyta species. Moreover, differences in cellular ultrastructure including chloroplast organization were investigated by transmission electron microscopy, comparing a detailed dehydration rehydration time course of poikilochlorophyllous X. schlechteri to homoiochlorophyllous X. elegans. This analysis revealed that desiccation-induced ultrastructural changes, such as vacuolation, chloroplast centralization, and starch degradation, typically observed in adult tissues, were also prevalent in the two-leaf seedlings of X. elegans and X. schlechteri. Notably, complete disassembly of the thylakoid membranes was observed in X. schlechteri but not in X. elegans. These results align with the significant reduction of monogalactosyldiacylglycerol, a major galactolipid involved in chloroplast function. The results of this study highlight differences between the poikilochlorophylly and homoiochlorophylly strategies, as well as conserved molecular responses to desiccation in Xerophyta species, providing insights into the evolution of VDT